CONSTRUCT VALIDITY OF NEGATIVE AFFECTS MEASURING TOOLS - Baquandi Lutvi Yoseanto (Media Inovasi Pendidikan dan Publikasi, 2025)
Negative affect is a general state of subjective stress and unpleasant conditions including anger, contempt, disgust, guilt, fear, and nervousness. This study aims to test the construct validity of the negative affect measurement tool. The approach in this study is a quantitative approach with a sample of 209 participants. Data collection was carried out by simple random sampling using a g-form questionnaire. The measuring instrument in this study was the Positive and Negative Affect Scale (PANAS) questionnaire by Watson, Clark and Tellegen (1988) which was adapted by the Research and Measurement section of the Faculty of Psychology, Tarumanagara University. The analysis method used the CFA test using a structural equation model. The results of this study indicate that the CFA model is fit with the following details: Chi Square = 431.229 (p = 0.000), RMSEA = 0.076, GFI = 0.842, CFI = 0.916, and TLI = 0.901. The model modifications carried out were by eliminating 5 manifest variables and covariancing 13 pairs of error variables. The results of this study can be used for the wider community, especially companies or organizations that want to see the level of negative affect of employees so that preventive and corrective actions can be taken.